Effective Utilization of a Small-Scale Municipal Solid Waste for Power Generation - Ujam, A.J; Eboh, F; Chime, T.O (Journal of Asian Scientific Research, 2013)
Quantity of small scale municipal solid waste available in each of the states of Nigeria was assessed and determined. Physical and Chemical characteristics of the various types of solid wastes were analysed and their values estimated. Thermal analysis of a small-scale municipal solid waste-fired steam generator was done. The analysis was based on the selected design parameters: operating steam pressure of 10 bar, with fuel consumption rate of 500 Kg/h and combustion chamber which utilizes mass burn incineration using water wall furnace. The plant is designed as a possible option for thermal utilization of rural and urban wastes in Nigeria. The average daily generation of MSW was considered in order to assess the availability of the material. The data were collected from Enugu State Waste Management Authority (ENSWAMA).This was calculated based on the state population, urbanization and industrialization strengths. Calculation of calorific value of the waste to determine the heat contents was carried out using two methods: Bomb calorimeter and Dulong’s formula. Some samples of the garbage were analyzed with bomb calorimeter in the National Centre for Energy Research & Development Laboratory, University of Nigeria, Nsukka. The calorific values obtained from this analysis were 12572.308 KJ/kg, 14012.05 KJ/kg, 21833.26 KJ/kg and 20551.01 KJ/kg for paper products, woods, plastics and textiles waste respectively, while the energy content obtained from the elemental composition of waste using Dulong’s formula was 15,101 KJ/kg .The maximum temperature of the furnace attained from the energy balance based on this value around the combustion chamber was 833.7 K and the amount of air required per kg of MSW was 8.66kg